Epistemology and methodology of the scientific investigation in the experimental philosophy of Galilean Galilei and Francis Bacon - Gómez Navarro, Ángel (2019)
The purpose of this study is to develop a comparative study about the manners of accessing the comprehension of the natural physical world as it is clear from the naturalistic and mechanistic theories of Galileo Galilei and Francis Bacon. In  fact, the new scientific rationality implied not only the consideration of epistemological and cosmological conceptions, but also the methodological ones by which the Galilean and Baconian philosophy presents them as a condition of possibility for obtaining Relevant knowledge. In this sense, to study the constitution of the new method of investigation and the elements that form it is constituted in an important contribution, so much for the human knowledge in general as for the scientific knowledge in particular.